A Method for the Analysis of African Swine Fever by Viral Metagenomic Sequencing - Ji, ChiHai; Jiang, JingZhe; Wei, YingFang; Wang, ZhiYuan; Chen, YongJie; Mai, ZhanZhuo; Cai, MengKai; Qin, ChenXiao; Cai, Yu; Yi, HeYou; Liang, Guan; Lu, Gang; et al. (Frontiers in Veterinary Science, 2021)
In 2018, there was an outbreak of African swine fever (ASF) in China, which spread to other provinces in the following three years and severely damaged China's pig industry. ASF is caused by the African swine fever virus (ASFV). Given that the genome of the African swine fever virus is very complex and whole genome information is currently inadequate, it is important to efficiently obtain virus genome sequences for genomic and epidemiological studies. The prevalent ASFV strains have low genetic variability; therefore, whole genome sequencing analysis provides a basis for the study of ASFV. We provide a method for the efficient sequencing of whole genomes, which requires only a small number of tissues. Pig spleens were crushed and homogenized using the macro virus group method, and the tissue and cell fragments were removed by low-speed centrifugation. The virus-like particles (VLPs) in the solution were purified and concentrated by filtration and over-speed centrifugation. After obtaining the relatively pure VLP sample, nucleic acids were extracted simultaneously by co-extraction of viral DNA (dsDNA, ssDNA) and RNA (ssRNA, dsRNA). Then, the database construction method was selected according to the genomic types of ASFV, and the whole ASFV genome was obtained through data filtering, host sequence removal, virus classification, data assembly, virus sequence identification, statistical analysis, gene prediction, and functional analysis. Our proposed method will facilitate ASFV genome sequencing and novel virus discovery.